Assessing Sustainability in Cattle Silvopastoral Systems in the Mexican Tropics Using the SAFA Framework - Fernanda Pérez-Lombardini; Karen F. Mancera; Gerardo Suzán; Julio Campo; Javier Solorio; Francisco Galindo (Animals, 2021)
The sub-humid native rainforest in Yucatan is one of the most endangered in Mexico. Cattle production is one of the main causes of land use change and silvopastoral systems are a feasible alternative. This work compares the sustainable performance of silvopastoral (native and intensive) and monoculture cattle farms in the state of Yucatan using the Sustainability Assessment for Food and Agriculture (SAFA) framework. Questionnaires and semi-structured interviews were applied in 9 farms. Responses were fed to the SAFA Tool to obtain sustainability polygons. Percentages of SAFA themes positively and negatively valuated were calculated. Native farms had positive ratings for Participation, Land, Biodiversity and Cultural Diversity, whereas intensive excelled on Holistic Management. Native farms had limited ratings for Decent Livelihood. Native farms (and one intensive silvopastoral farm) had the highest percentages of themes positively valuated compared to monocultures (and one intensive silvopastoral farm), which scored the lowest. Positive evaluations identified native systems as an option for sustainable production; however, areas of opportunity in all farms were discovered. This is the first comparative study using SAFA to evaluate differences in farming systems in the Mexican tropics, providing valuable information to generate policies and incentives on sustainable livestock production, as well as for improving evaluation tools for local application.